PROTOTYPE PALANG PARKIR OTOMATIS SATU PINTU MENGGUNAKAN SENSOR ULTRASONIK BERBASIS ARDUINO UNO - Darmawan, Erwin (LPPM Politeknik Pajajaran ICB Bandung, 2024)
The use of ultrasonic sensors is widely used in automation systems. Its uses include detecting an object, measuring the distance of an object and calculating the number of an object and so on. In making this tool, an ultrasonic sensor is used to detect the presence of an object in the form of a vehicle, the reading results are forwarded to the Arduino microcontroller for processing, then forwarded by the Arduino Uno microcontroller to the Servo Motor which functions to open and close the parking gate. This prototype uses a parking barrier for vehicle entry and exit so it uses two ultrasonic sensors, one servo motor and an Arduino Uno microcontroller.